Prototexto, narrativa poética da ciência: uma estratégia de construção do conhecimento e religação de saberes no ensino de física - Araujo, Valmir Henrique de (2009)
In this thesis I present the prototexto notion and to I base as a complex system while strategy of knowledge construction and reconexion of you know in physics teaching. Prototexto is a poetic narrative of the science, proposal and used initially as "instrument of creative" learning for students apprentice of science of the medium and technical teaching of the Vitória da Conquista's CEFET-BA, in the period of 1997-2004. Later become pregnant as a strategy of knowledge construction, in the Universidade Estadual da Bahia - UESB, the prototexto notion configures a complement to the mathematical formulation. The proposal of a poetic narrative of the science is that the apprentice of science starts to organize in an aesthetic-literary way your knowledge, dispersed in disciplines, starting from a theme of the physics. The prototexto emerges of my reflections concerning the classic science, identified for Edgar Morin as tends a thought excessively numeric, and that it has been reproduced in physics teaching, in most of the schools, limiting him/it to an order pattern with the mistake absence. They are operations of the prototexto: the poetic language, the pedagogic stamp, the unfinished of the argument, the system character and the apprentice's of science inclusion as subject implicated in the construction of the knowledge. the theoretical foundations are based Morin's proposition of the method as strategy, the beginning of the complementarity of Niels Bohr in conceiving excluding categories as face of a same phenomenon and the conception of creative time of Ilya Prigogine that enunciates the alliance among the nature and the man that it describes her